Ecotoxicity of two organic UV-filters to the freshwater caddisfly Sericostoma vittatum - Campos, Diana; Gravato, Carlos; Fedorova, Ganna; Burkina, Viktoriia; Soares, Amadeu M V M; Pestana, João L T (Environmental pollution (Barking, Essex, 2017)
Organic ultraviolet filters (UV-filters) used for protection against radiation in personal care products and other materials (e.g. textiles, plastic products) are considered emerging contaminants of aquatic ecosystem. Benzophenone-3 (BP3) and 3-(4-methylbenzylidene)camphor (4-MBC) are the most commonly used organic UV-filters and have been reported in freshwater environments due to contamination through discharges from wastewater treatment plants and swimming pools or by direct contamination from recreational activities. Our aim was to evaluate the ecotoxicological effects of these UV-filters using the freshwater caddisfly Sericostoma vittatum' biochemical biomarkers and energy processing related endpoints (feeding behaviour, energy reserves and cellular metabolism). In laboratory trials, both compounds induced feeding inhibition of S. vittatum at 3.55 mg/kg of BP3 and at concentrations ≥2.57 mg/kg of 4-MBC, decreased carbohydrates content at 3.55 and 6.95 mg/kg of BP3 and 4-MBC respectively, and increased total glutathione levels at concentrations ≥1.45 and 1.35 mg/kg of BP3 and 4-MBC respectively. No significant effects were observed on endpoints associated with oxidative stress, antioxidant defences, phase II biotransformation or neurotoxicity after exposure to the two UV-filters. Our results show that environmental relevant concentrations of BP3 and 4-MBC, can negatively impact freshwater insects and demonstrate the importance of monitoring the ecological effects of organic UV-filters using non-model invertebrate species.
Keywords: plavecké bazény; hmyz; Feeding behaviour; benzofenony; Swimming Pools; Personal care products; zvířata; kafr; Insecta; sladká voda; přípravky chránící proti slunci; Freshwater insects; 4-MBC; Sunscreening Agents; Fresh Water; Benzophenones; Sunscreens; Water Pollutants, Chemical; Animals; BP3; Camphor; chemické látky znečišťující vodu